PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - M. Hendri Yan Nyale; Henni Rolita Gultom (POLITEKNIK LP3I JAKARTA, 2024)
The research was conducted to see the effect of the variables of profitability, leverage, and company size as independent variables on the timeliness of financial report submission as the dependent variable. The profitability variable in this study uses ROE as a measuring tool, for leverage using DER as a measuring tool, and finally Ln is used as a measuring tool for the company size variable. This research uses the property and real estate sector industry listed on the IDX for the 2020-2022 period. 48 companies were obtained for the population so that the research sample was 144. This research uses quantitative methods and uses secondary data sourced from the IDX. The sampling process applies purposive sampling technique. The analysis test processed using the SPSS 25 application shows that there is a simultaneous influence on profitability and leverage, and company size on the timeliness of financial report submission. It was found that profitability and leverage did not have a significant influence on the timeliness of submitting financial reports, while company size showed a positive influence on the timeliness of submitting financial reports.. Keywords: Leverage, Company Size, Timeliness of Submitting Financial Statements